Integrative insights into salinity stress mitigation and physio-molecular mechanisms in sugarcane - Dhansu, Pooja (The Indian Journal of Agricultural Sciences, 2026)
Sugarcane is a highly prevalent crop in tropical and subtropical regions around the globe. The present study was conducted to explore the salinity tolerance potential of high yielding available genotypes and to characterize the biochemical and molecular traits contributing to tolerance and to identify the salt tolerant sugarcane clones for the use of farmer communities and as donors in future breeding programs. Five Co-canes (Co 0118, Co 13035, Co 15023, Co15025, and Co 0238) were irrigated with three levels of salinity stress (i.e. moderate, severe, and extreme) anda control without salt stress. Continued irrigation with saline water (ECiw ~ 4, 8, and 10 dS m⁻¹) resulted in a progressive increase in soil electrical conductivity (ECe) throughout the crop cycle. At harvest, soil ECe increased from 0.81 dS m⁻¹ in the control to 2.89, 6.91, and 8.79 dS m⁻¹ under ECiw ~ 4, 8, and 10 dS m⁻¹, respectively, indicating considerable salt accumulation in the root zone under higher salinity levels. Physiological changes, antioxidant activities, salt overly sensitive (SOS) genes, and ion transporters genes expression responses were assessed under varying salinity stress. Genotype Co 15023 exhibited the higher chlorophyll content and SPAD reading in Co 0118 genotype. The antioxidant enzyme activities were highest observed in genotype Co 13035 under ECiw - 4, 8 and 10 dS/m, respectively with respect to control. The SOS, NHX1, and HKT genes had higher expression (FC≥5; P≤0.05) in genotype Co 13035 compared to the control. These results suggested that Co 13035 promising genotype for salt stress tolerance in sugarcane, highlighting its potential for farmer use and future breeding programs.